Building Loyalty Through Education on Passenger Trust in Low Cost Airlines Indonesia, The Role Of Service Quality And Passenger Satisfaction - Mandasari, Nur Fitriayu; Radjab, Enny; Ashdaq, Muhammad; Nadir, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The study aims to investigate how service quality contributes to passenger loyalty in LCA Indonesia, considering satisfaction and trust. A survey was conducted with 400 respondents who used LCA services for domestic flights at Sultan Hasanuddin Airport in Makassar between 2021 and May 2022. Structural Equation Modeling (SEM) was employed for data analysis. The results indicate that service quality, passenger satisfaction, and trust are crucial in shaping loyalty. Satisfying services have the potential to foster trust, leading to passenger loyalty. Satisfaction and trust act as effective mediators of service quality and passenger loyalty. The findings highlight the importance of delivering high-quality services that meet passenger expectations and generate satisfaction. LCA Indonesia can build trust and establish a loyal customer base by exceeding customer expectations. Service quality is vital for providing positive experiences to passengers. Understanding the mediating roles of satisfaction and trust is also key. LCA Indonesia can enhance passenger loyalty by prioritizing service quality, improving satisfaction levels, and building trust among passengers. Addressing these factors strengthens the airline's competitive position and ensures long-term customer loyalty in a highly competitive market.